Attachment and Aggressive Manifestations in Younger Adulthood - "Preliminary Findings" - Tatiana Lorincová (Psychology and its Contexts, 2014)
The main topic of the contribution was comparison between retrospective attachment (emocional warmth and rejection) and aggressive manifestations (physical aggressivness, verbal aggressivness, anger and hostility) among younger adulthood. Bowlby's theory of attachment was that once a core attachment style develops in an infant, it will influence and shape the nature of all intimate relations for the individual moving forward throughout the infant's life cycle. Authors Mikulincer and Shaver (2011) explain how these primary attachment experiences would affect future emotional, cognitive and behavioral processes. Secure adolescents, in comparison to insecure ones are perceived as being less aggressive. Research has pointed out that secure parental attachment promotes adaptive psychological functioning. The direct relationship between attachment security and aggressive/delinquent behaviour is in line with prior evidence that secure adolescents rate higher in terms of emotional and social adjustment, enjoy more positive relationships with their family and peers, and are less likely to engage in externalizing problems, such as antisocial and aggressive behaviours. On the other hand, insecure attachment is connected with aggressive and externalizing behaviour. Hypotheses were formulated on the base of theoretical background and our assumption was, that younger adults with emocional warmth attachment will have lower level of aggressive manifestations (physical aggression, verbal aggression, anger and hostility) than younger adults with rejectional attachment. We used two standardized questionnaires for data collection, s.E.M.B.U. Questionnaire, which measured retrospective attachment (emocional warmth and rejection) and Questionnaire of Aggressivness, which measured aggressive manifestations. We used statistical analysis and we found statistically significant differencies, which are preliminary findings from broader research, between emocional warmth attachment and rejectional attachment in physical aggressivness with F = 13,53 , anger with F = 11,23 and hostility with F = 24,96 and in all cases was statistical significance p ≤ 0,05. We did not find significant differencies between emocional warmth attachment and rejectional attachment in verbal aggressivness with p = 0,13 a F = 2,12. Hypotheses were confirmed and it is possible to agree with previous researches, that secure attachment or emocionally warmth attchment is associated with appropriately and insecure attachment or rejectional attachment is associated with aggressive behaviour.